Evaluadores N°3 - Tonon, Graciela (Journal de Ciencias Sociales, 2014)
JOURNAL DE CIENCIAS SOCIALES EVALUADORES Año 2, NUMERO 3, 2014. Dr. Anibal Biglieri, Universidad de Kentucky, USA. Dra. Cecilia Cadena Inostroza, El Colegio Mexiquense, México. Dr. Ricardo Fletes Corona, Universidad de Guadalajara, México. Dr. Napoleón Murcia Peña, Universidad de Caldas, Colombia. Dr. Antonio López López, Colombia. Dr. Norberto Méndez, Universidad de Buenos Aires, Argentina. Dra. Lucia Puppo, CONICET, Argentina. Dr. Mariano Bartolome, Universidad de Belgrano, Argentina. Dra Irma De Filippis, Universidad Nacional de La Matanza, Argentina. Mag. Norma del Rio, Universidad Autónoma Metropolitana, México. Mag. María del Valle Correa Rojas, Universidad Nacional de Salta, Argentina. Lic. Ernesto Zambrini, Universidad de Palermo, Argentina.